A Supramolecular Approach to the Preparation of Nanographene Adlayers Using Water‐Soluble Molecular Capsules. (23rd October 2018) - Origuchi, Sakura; Kishimoto, Mai; Yoshizawa, Michito; Yoshimoto, Soichiro
Abstract: Polycyclic aromatic hydrocarbons (PAHs) are excellent building blocks for the creation of two‐dimensional (2D) nanosheets. However, large PAHs tend to exhibit poor or no solubility in organic solvents and water. To overcome this issue, we employed water‐soluble micellar capsules consisting of V‐shaped amphiphilic molecules. Characteristic electrochemical behavior was observed in 0.1 m H2 SO4 in the presence of the water‐soluble capsules containing PAHs, such as ovalene, circobiphenyl, and dicoronylene. Furthermore, under these conditions, PAHs were released from the capsules, resulting in the formation of a 2D adlayer of PAHs at the electrochemical interface. Finally, using electrochemical scanning tunneling microscopy, we demonstrate that our molecular containers based on water‐soluble molecular capsules allow the facile preparation of 2D PAH adlayers in addition to structurally controlling nanostructure formation on Au surfaces.